2006
DOI: 10.1115/1.2217751
|View full text |Cite
|
Sign up to set email alerts
|

Drag and Heat Transfer Reduction Phenomena of Drag-Reducing Surfactant Solutions in Straight and Helical Pipes

Abstract: Flow drag and heat transfer reduction phenomena of non-ionic aqueous surfactant solutions flowing in helical and straight pipes have been experimentally investigated at surfactant solution concentration range of 250-5000ppm and temperature range of 5-20°C. The helically coiled pipes have curvature ratios range of 0.018–0.045. Experimental findings indicate that the friction factors and the heat transfer coefficients of the surfactant solution in helical pipes are significantly higher than in a straight pipe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…This is motivated by the leading study of Usui et al [41,39], who showed the effectiveness of the mixture of the nonionic surfactant solution and the sodium salicylate as drag-reducing additives, in which the available data were restricted and the degradation property remained an open question. The studies on the drag-reducing ability of the mixture of the amineoxide nonionic and betaine zwitterion surfactants have been also reported [3,7]. Broniarz-Press et al [5] reviewed that the mixed drag reducer system (polymer/ surfactant, surfactant/surfactant) caused an increase of the system stability and of the temperature range in which the additives were most effective.…”
Section: Introductionmentioning
confidence: 96%
“…This is motivated by the leading study of Usui et al [41,39], who showed the effectiveness of the mixture of the nonionic surfactant solution and the sodium salicylate as drag-reducing additives, in which the available data were restricted and the degradation property remained an open question. The studies on the drag-reducing ability of the mixture of the amineoxide nonionic and betaine zwitterion surfactants have been also reported [3,7]. Broniarz-Press et al [5] reviewed that the mixed drag reducer system (polymer/ surfactant, surfactant/surfactant) caused an increase of the system stability and of the temperature range in which the additives were most effective.…”
Section: Introductionmentioning
confidence: 96%
“…Other methods such as fluted tube heat exchanger [20], wire meshes [37], static mixers [12], and impinging jets [38] were aimed to temporarily break the wormlike micelles; they actually also disturbed the flow, but their relative contributions to enhanced heat transfer are not clear. To disturb the flow, still other methods employed were contracted channel [39], grooved tubes [40], wire coils [41], helical pipes [42], and vortex generators [43].…”
Section: Advances In Mechanical Engineeringmentioning
confidence: 99%
“…It has been widely reported in literature that heat transfer rates in helical channels are higher as compared to that of straight ones [1]. Numerical or experimental studies on helical coiled channels with a circular cross section have been conducted.…”
Section: Introductionmentioning
confidence: 99%